Infrastructure and Income Distribution in ASEAN-5 : What are the Links? - Seneviratne, Dulani (IMF Working Papers; Working Paper ;, 2013)
Adequate infrastructure has long been viewed as an important factor in economic development. Based on regressions covering 76 advanced and emerging market economies, this paper estimates the impact of infrastructure and investment on income distribution. It finds that better infrastructure, both quality and quantity, promotes income equality, while the link between investment and income distribution is weak.